2017
DOI: 10.3168/jds.2016-12273
|View full text |Cite
|
Sign up to set email alerts
|

A survey of dairy calf management practices among farms using manual and automated milk feeding systems in Canada

Abstract: Dairy calves in North America traditionally are housed individually and fed by manual milk feeding (MMF) systems with buckets or bottles. Automated milk feeders (AMF) allow for more natural milk feeding frequencies and volumes, and calves are usually housed in groups. The objectives of this study were to (1) determine the prevalence of various milk-fed calf management and feeding practices and (2) compare these practices between dairy farms using MMF and AMF systems. A national online survey was performed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 37 publications
2
48
1
1
Order By: Relevance
“…Moreover, producers from our study also indicated that their farm size was too small to justify the purchase and the use of an automated milk feeder. This result is parallel to what we found regarding features of surveyed farms, where larger farms were more likely to have AMF compared with small farms (Medrano-Galarza et al 2017). Manufacturers promote that an AMF can supply a group of approximately 25 calves per feeding station (Käck and Ziemerink 2010).…”
Section: Farms Feeding Milk Manuallysupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, producers from our study also indicated that their farm size was too small to justify the purchase and the use of an automated milk feeder. This result is parallel to what we found regarding features of surveyed farms, where larger farms were more likely to have AMF compared with small farms (Medrano-Galarza et al 2017). Manufacturers promote that an AMF can supply a group of approximately 25 calves per feeding station (Käck and Ziemerink 2010).…”
Section: Farms Feeding Milk Manuallysupporting
confidence: 82%
“…In addition, the survey was advertised in dairy cattle magazines and on social media. Detailed description of the survey development, administration, and data handling is presented in Medrano-Galarza et al (2017). Briefly, the survey consisted of two questionnaires with closed-and open-ended questions; one questionnaire was for producers using MMF systems [i.e., milk offered via open bucket or teat (bottle, bucket, and milk bar)], and another questionnaire was for producers using AMF systems (i.e., computer-controlled systems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many dairy producers prefer to introduce calves to an AMF as soon as possible (Jorgensen et al, 2017;Medrano-Galarza et al, 2017a) without clear evidence Figure 3. Mean daily milk intake (±SE) across the 5 stages of the milk feeding period (from 1 to 60 d of age) for 60 calves introduced to a group with an automated milk feeder at 5 d of age (conventional introduction) and before 24 h of age (early introduction).…”
Section: Discussionmentioning
confidence: 99%
“…Although research (Svensson and Liberg, 2006;Jensen, 2007) suggests that later introduction (i.e., >2 wk of age) to the group pen may be preferable in terms of calf health and farm labor, recent data on commercial dairy farms in North America indicate that the median age of introduction to group pens with AMF is 5 d and ranges from <1 to 14 d (Jorgensen et al, 2017;Medrano-Galarza et al, 2017a; mean group size was 17 calves and ranged from 6 to 60). This may stem from producers seeking to minimize the labor required for manually feeding milk to calves when using AMF.…”
Section: Introductionmentioning
confidence: 99%